Identifying grass-legume bicultures to increase above and belowground biomass production and improve traditional fallows in crop rotations of the Andean Highlands - Meza Retamozo, Katherin Paola, author; Fonte, Steven, advisor; Schipanski, Meagan, committee member; Davis, Jessica, committee member (Colorado State University. Libraries, 2021)
In the high Andes of Peru, intensification of crop rotation and agricultural land-use is reducing the practice and duration of traditional fallow (based on natural establishment of native vegetation). These fallows represent one of the main traditional soil management practices to sustain long-term productivity, while also providing key forage resources in these mixed crop-livestock systems. Improved forage-based fallows, with the intentional seeding of more productive annual and perennial forages, offer great potential for producing forage and contributing to soil restoration under intensified contexts; however, there remains a gap in knowledge about which plant species can best optimize tradeoffs between forage production and belowground inputs to support long-term soil fertility and contribute to the multifunctionality of Andean agroecosystems. To address this issue, a pot study was conducted with two contrasting soils to evaluate the above and belowground productivity of all possible grass-legume pairs involving five grasses (oat (Avena sativa), ryegrass (Lolium multiflorum), festulolium (Lolium x Festuca genera), brome grass (Bromus catharticus), and orchardgrass (Dactylis glomerata), and four legumes (vetch (Vicia dasycarpa ), red clover (Trifolium pratense), black medic (Medicago lupulina), and alfalfa (Medicago sativa)) in comparison to the performance of each species in monoculture. Grass-legume bicultures resulted in significant overyielding, producing 65% and 28% more total dry biomass and total N uptake on average than species in monoculture, respectively. Grass-legume shoot biomass production yielded 67% more compared to monocultures, while root biomass was on average 58% higher in bicultures than in monocultures. For aboveground biomass, production differences between grass-legume bicultures were significantly influenced by the species of legume present, while belowground biomass was more affected by the grass species present in the bicultures. Roughly 80% of the mixtures achieved a mean land equivalent ratio (LER) > 1.0. When examining total biomass production, the most successful bicultures were oat-vetch (LER=1.87), vetch-festulolium (LER=2.31), vetch-orchardgrass (LER=1.87), oat-red clover (LER=1.62), and red clover-ryegrass (LER=1.46). When examining partial LERs (the component of the LER attributed to each species), we found that overyielding in bicultures was mainly driven by increases in the biomass of the component grass species. Our findings suggest that mixtures of key functional species (e.g. grass and legume, annual and perennial species) offer greater promise in improved fallows compared to monocultures of the respective species. Additionally, I suggest that strategically designed improved fallow mixtures, with emphasis on perennial species that support long-term root inputs, can best support soil health and the multifunctionality of Andean agroecosystems.